Сільськогосподарські відносини у Миколаївській генеральній окрузі в роки німецько-румунської окупації південної України (1941 -1944 р.). - Вишневський, Сергій Анатолійович; Vyshnevsky, Sergiy A. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Дана стаття присвячена аналізу становлення та розвитку сільськогосподарських відносин у Генеральній окрузі Миколаїв, в роки німецької окупації (1941 – 1944 рр.) південної України. Розглянуто заходи окупаційної влади здійснені у цьому напрямі. Приділено, також, увагу навчальним закладам с/г спрямування, які діяли в роки окупації. Подано оцінку стану сільського господарства Миколаївської генеральної округи.This article focuses on the analysis of the formation and development of agricultural relations in the General District of Nikolaiv, during the German occupation of South Ukraine (1941 - 1944). The article analyzes measures of the occupation authorities carried out in this area, which include Congress of livestock breeders of Reichcommissariat of Ukraine, that took place in Kirovohrad, meetings of farms and stations. Special attention is paid to educational institutions of agricultural character, that acted during the occupation, such as gardening schools, colleges and Kherson high school agronomists. Agriculture of Nikolaev general region is studied. The basic directions of livestock and crops growing that the occupation authorities gave the preference are analyzed.
Agricultural relations in the Mykolayiv general county during the german-romanian occupation of south Ukraine (1941 -1944).
Keywords: Генеральна округа; господарство; окупація; врожай; громадське господарство; колгосп; General vicinity; economy; occupation; harvest; public sector; farm